Editorial Note Vol.1 - Chhetri, Gana Raj (Nepalese Journal of Management Research, 2021)
Nepalese Journal of Management Research (NJMR) is an open access, peer-reviewed, and refereed journal published annually with the aim to provide an intellectual platform for the academia, management researchers, and management students to publish their original works. NJMR publishes quality research articles in the fields of business administration and allied areas of management. The journal publishes research papers in the fields of financial management, Accountancy, Marketing, General Management, Banking, Business, managerial economics and so on. The journal is published in both printed and online versions. Special Issues devoted to important topics in business and social science will occasionally be published. Business innovation and research strategies, tactics and tools of both theoretical and practical nature are welcome. The challenging aspect is that female participation in research is very few in spite of great encouragement of the research division. Hopefully, it will be increased in the next issue. Chairman of the Board Mr. Jagannath Poudel, and Principal Mr. Jagadishwar Khanal have always inspired teachers to be involved in the research activities. Former Principal Mr. Chun Narayan Shrestha and Ex- Principal Mr. Shiva Prasad Poudel have played very important role in bringing out this issue in time. I would like to thank Chairman of the Board, Mr. Jagannath Poudel, and Principal Mr. Jagadishwar Khanal, for their ongoing commitment to the standards to which the journal aspires. I would like to take this opportunity to thank all prominent members of editorial board Dr. Suraksha Shrestha and Dr. Suroj Tandan, advisors and peer review team for joining us in this fascinating and promising academic development.